THE IMPORTANCE OF THE LEVEL OF SOCIAL SUPPORT IN THE DEVELOPMENT OF POST-TRAUMATIC STRESS DISORDER (PTSD) - Shukurlayeva Mashxura Farxodovna (World Scientific Research Journal, 2025)
Abstract: This article examines the importance of social support in the development of post-traumatic stress disorder (PTSD) and its role in reducing negative psychological consequences. The study analyzed the influence of the social environment, family and friendly relations, as well as the level of social resources on the formation and duration of PTSD symptoms. The results showed that a high level of social support contributes to the recovery of mental state after traumatic events, reduces stress, and improves mental health. The article emphasizes the need to develop social support systems in the fight against PTSD and proposes new approaches to psychological support strategies.